Climate patriots? Concern over climate change and other environmental issues in Australia. (August 2017) - Tranter, Bruce; Lester, Libby
Echoing the anti-pollution and resource conservation campaigns in the United States in the early-to-mid-twentieth century, some scholars advocate mobilising support for environmental issues by harnessing the notion of environmental patriotism. Taking action to reduce the impact of global warming has also been cast as a patriotic cause. Drawing upon quantitative data from a recent national survey, we examine the link between patriotism and environmental attitudes in Australia, focussing upon climate change. We find that patriotism has a largely neutral association with concern over environmental issues, with the exception of climate change and, to a lesser extent, wildlife preservation. Expressing concern over climate change appears to be unpatriotic for some Australians. Even after controlling for political party identification and other important correlates of environmental issue concerns, patriots are less likely than others to prioritise climate change as their most urgent environmental issue and less likely to believe that climate change is actually occurring.